KNOWLEDGE AND ATTITUDE TOWARD E-PHARMACY AMONG THE PHYSICIANS OF SOUTH RAJASTHAN, INDIA: A PILOT SURVEY - YADAV, ARVIND KUMAR; PICHHOLIYA, MEENU; SHETH, HAIYA; GUPTA, SANGITA; CHOUDHARY, SAVITA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the knowledge and attitude of physicians of South Rajasthan, India, toward e-pharmacy. Methods: After obtaining ethical approval, this cross-sectional questionnaire-based study was carried out for 6 months at a tertiary care teaching hospital. Physicians willing to participate were included in the study. The study questionnaire comprised 10 questions which were validated by experts. Physicians were requested to fill up the questionnaire in the presence of researcher and return it back. Data were analyzed using Microsoft Excel Office 365. Results: A total of 170 questionnaires were analyzed. Male/female ratio of the physicians was 1.24:1. About 91.76% of physicians had heard of e-pharmacy but only 22.35% had ever used it. About 89.41% of physicians had never asked patients to buy medicines from e-pharmacy. About 67.64% of physicians considered e-pharmacy as ethical. However, 56.47% of physicians thought that e-pharmacy is risky. Conclusion: Physicians must remain up-to-date about these recent technologies like e-pharmacy; as it is expected to become much more common in the next few years. Ethical and non-risky methods should be adopted for the same by them. Overall, a balance should be maintained while opting for online pharmacy.